Comparison of Scrotal Hitch Technique and Conventional Scrotal Dressing in Reducing the Postoperative Scrotal Oedema in Inguinoscrotal Surgeries: A Non Randomised Clinical Study - Balaji Rajavarman; Manigandan Raju; Umesh Raj Somasundaram; AS Sangeethapriya (Journal of Clinical and Diagnostic Research)
Introduction: Inguinoscrotal swellings, including hernias and hydroceles, are the most common complaints in the surgical outpatient department. Hernioplasty and eversion of the sac are the most common elective procedures for inguinoscrotal swellings. Scrotal oedema is one of the complications following the surgery, which increases the patient’s morbidity.